Penyalahgunaan Nama Pribadi Pemegang Saham Dan Komisaris Oleh Direksi Selaku Pemegang Saham Mayoritas - Fiona Chrisanta; Nyulistiowati Suryanti; Ema Rahmawati (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
The deed of incorporation of a company serves as the identity of the company because it contains the articles of association and other information which is of course related to the establishment of the company, as well as its organs. However, over time, irresponsible parties often abuse the process of establishing and/or amending these laws. The purpose of this research is to look at and evaluate the regulations regarding the accountability of a director as the majority shareholder who abuses their authority over the procedure for amending the articles of association without an EGMS. This research uses normative juridical. The results to be aimed at are knowing the accountability of the directors as the majority shareholder for changes to the company's management structure without holding an EGMS and implementation of the Limited Liability Company Law regulations for changes to the company's management composition.